2023
DOI: 10.1021/jacs.3c00722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of an Anti-van’t Hoff/Le Bel Compound with a Planar Tetracoordinate Silicon(II) Atom

Abstract: For a long time, planar tetracoordinate carbon (ptC) represented an exotic coordination mode in organic and organometallic chemistry, but it is now a useful synthetic building block. In contrast, realization of planar tetracoordinate silicon (ptSi), a heavier analogue of ptC, is still challenging. Herein we report the successful synthesis and unusual reactivity of the first ptSi species of divalent silicon present in 3, supported by the chelating bis(N-heterocyclic silylene)bipyridine ligand, 2,2′-{[(4-tBuPh)­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Another example utilizing a rigid tetradentate ligand to access planar silicon species is Driess’ planar silicon( ii ) complex 33 supported by a bis(N-heterocyclic silylene) bipyridine ligand. 130 While not strictly within this review's scope due to the planarity being a result of additional coordination, it is noteworthy that this species shows not only planarity but also a very wide angle between the amidinate groups of approximately 111°. This dication features a planar central silicon atom with a lone pair of electrons localized in the silicon p z orbital, in contrast to most silylenes in which the lone pair is localized in an s orbital.…”
Section: Compounds With a Group 14 Central Elementmentioning
confidence: 95%
See 1 more Smart Citation
“…Another example utilizing a rigid tetradentate ligand to access planar silicon species is Driess’ planar silicon( ii ) complex 33 supported by a bis(N-heterocyclic silylene) bipyridine ligand. 130 While not strictly within this review's scope due to the planarity being a result of additional coordination, it is noteworthy that this species shows not only planarity but also a very wide angle between the amidinate groups of approximately 111°. This dication features a planar central silicon atom with a lone pair of electrons localized in the silicon p z orbital, in contrast to most silylenes in which the lone pair is localized in an s orbital.…”
Section: Compounds With a Group 14 Central Elementmentioning
confidence: 95%
“…This dication features a planar central silicon atom with a lone pair of electrons localized in the silicon p z orbital, in contrast to most silylenes in which the lone pair is localized in an s orbital. 130 The compound is reversibly interconverted with a hexacoordinate silicon( iv ) species by reaction with I 2 and a reduction to return to 33 . 130…”
Section: Compounds With a Group 14 Central Elementmentioning
confidence: 99%
“…By contrast, for heavier tetrel derivatives, several organosilicon compounds featuring planar (or nearly planar) geometry at the Si centre were very recently reported. They include: (a) tetrasilabicyclo[1.1.0]butanes with an exceptionally long Si–Si bridge (treated as either π-single bond 13,14 or 1,3-biradicaloid interaction 15 ) and planarity around the bridgehead Si atoms; (b) Mo and W bimetallic complexes in which a planar tetracoordinate Si centre is embedded in a tricyclic trapezoidal M–C–C–M (M = Mo, W) core; 16 (c) bis(NHSi)silylene, in which a planar tetracoordinate silylene centre is intramolecularly stabilized by a bipyridine ligand; 17 (d) organosilicon compound, in which a planar tetracoordinate Si atom is rigidly fixed within the calix[4]pyrrolato ligand, thus representing a unique example of a square-planar silicon( iv ) derivative with remarkably small HOMO–LUMO energy gap achieved upon planarization at Si. 18…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, a variety of compounds containing anti-van’t Hoff/Le Bel ptSi were successfully synthesized, exhibiting remarkable stability at room temperature . Just recently in 2023, Shan et al reported the first experimental synthesis of isolable metal-free ptSi­(II) dication . Moreover, first-principles calculations have confirmed that dispersed Si with a ptSi motif can act as a fundamental building block for 2D sheets in extended systems, and the incorporation of ptSi gives rise to remarkable electronic properties in 2D nanomaterials. , …”
mentioning
confidence: 99%
“…20 Just recently in 2023, Shan et al reported the first experimental synthesis of isolable metalfree ptSi(II) dication. 21 Moreover, first-principles calculations have confirmed that dispersed Si with a ptSi motif can act as a fundamental building block for 2D sheets in extended systems, and the incorporation of ptSi gives rise to remarkable electronic properties in 2D nanomaterials. 22,23 Despite the notable advancements mentioned above, two intriguing and pivotal aspects of ptSi remain to be clarified.…”
mentioning
confidence: 99%